The Influence of The Role of Parents on Dental and Oral Health From The Severity of Dental Caries in Deaf Children Aged 7-14 At SLB N 1 Bantul - Evinna Juliana Subroto; Ratih Larasati; Isnanto (International Journal of Advanced Health Science and Technology, 2024)
Deaf children in their limitations really need the role of parents. Parental behavior is very important in the formation of behaviors that support or do not support children in maintaining dental and oral hygiene. Dental caries is a disease of dental tissue that is characterized by tissue damage, starting from the surface of the tooth (recess, fissure, and interproximal area) extending towards the pulp. The problem of high DMF-T scores in deaf children aged 7-14 years at SLB N 1 Bantul. The purpose of the study was to determine the influence of the role of parents on dental and oral health from the severity of dental caries in deaf children aged 7-14 at SLB N 1 Bantul. This type of analytical research research with a cross sectional design. The research target was parents (fathers/mothers) and deaf children aged 7-14 years at SLB N 1 Bantul with a total sampling technique using the purposive sampling method. Data collection instruments, questionnaire sheets and examination sheets. The data analysis technique used is the Spearman-rank test. The results of the study showed that the p value (0.020) < 0.05, it can be concluded that there is an influence of the role of parents on dental and oral health reviewed from the severity of dental caries in deaf children aged 7-14 years at SLB N 1 Bantul with sufficient closeness.